Control Code Multiple Encryption Algorithm on Satellite-to-ground Communication - Liu, Jinlong; Yang, Zhutian; Wu, Zhilu; Yin, Zhendong; Jiang, Xu; Fu, Yanyuan (Mobile networks and applications, 2019)
The transmission security between ground station and satellite is challenging. Some existing multistep algorithms leave lots of loopholes for eavesdropping and attacking in satellite-to-ground communication. For high security, optical communication is a promising solution. In this paper, we propose a control code multiple encryption algorithm (CCMEA) for the single-photon-transmission between satellite and ground station. CCMEA can utilize the control code to respectively encrypt three cognitive optimization sections: loop iteration, polarization coding and order rearrangement, and simulation shows that CCMEA can realize one step transmission to decrease loopholes compared with multistep encryption algorithm. In addition, we design a security detection method by combining the decoy photon analysis and the quantum bit error rate (QBER) analysis. The numerical results show that CCMEA can reduce the security threshold by 27 % compared with multistep encryption algorithm of BB84 scheme. Finally, for satellite-to-ground communication, we construct an analytic QBER model on CCMEA with four factors: quantum channel transmission rate, single-photon acquisition probability, measurement factor and data filtering factor. The result demonstrates the effectiveness of CCMEA on satellite-to-ground communication.